Piercing Liability in the Polish and German Legal Systems - Modrzejewska, Klaudia (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2025)
Piercing liability is one of the most important and interesting issues in company law. It refers to a process of “breaking” or even “piercing” the legal separateness of several related companies in order to provide legal protection for the interests of creditors of one of them. This issue is linked to the improper, and consequently undesirable, exploitation of the distinctiveness of a subsidiary company by the parent that controls it. In a nutshell, piercing liability is seen as a legal instrument whose purpose is to give protection to creditors, even if this involves disregarding the legal personality of a particular company or even rejecting the legal and organisational personality of the entity. It is a response to the abuses of those who misuse legal personality, but also a response to the needs of the modern economy. At the same time, it raises serious doubts and even controversies in every legal system in which it is applied. This is due to the fact that clear criteria for the application of piercing liability have not been formulated in any of the legal systems mentioned. In the article, I will characterise the reasons for the introduction and development of piercing liability in the Republic of Poland and in the Federal Republic of Germany.